Learning to perform: A conversation analytic systematic review of learning and teaching practices in performing arts lesson interactions. (March 2021) - Ivaldi, Antonia; Sanderson, Alice; Hall, Gareth; Forrester, Michael
Abstract: This review synthesizes conversation analysis research examining multimodal performing arts interactions in learning and teaching contexts. It shows how the art itself is integrated into the learning dialogue and how it is integral to getting the business of learning and teaching done. Twenty-three publications met the criteria: conversation analytical multimodal research in performing arts lessons and rehearsals, with participants of all ages. The review highlights the developing field of conversation analysis in the performing arts over the last five years in particular. Nine practices were identified: (1) establishing and manipulating rhythm, space and timeframe, (2) making corrections, (3) miming and mirroring to provide information and understanding, (4) highlighting movements and demonstrations, (5) teacher/conductor controlling beginnings/restarts/end of activities, (6) cues for where to start/pick up from, (7) students showing understanding, (8) getting ready to perform, and (9) making learning inclusive and collaborative. As the practices were predominantly teacher led, students have little opportunity to engage in the learning dialogue and drive their own learning – responding mainly with performance. More active learning opportunities need to be created by teachers and conductors so that students can generate their own practices for learning.